Menerobos Prinsip Kerahasiaan Bank Guna Mencegah Risiko Gagal Bayar dan Kejahatan Lintas Negara Menggunakan Letter of Credit - Diah Rahma Kusumaningrum; Pujiyono Pujiyono (University of Udayana, 2020)
L/C is a means of payment for international trades which, to date, is considered to have a high level of security due to the sharing of risks for the parties involved. What distinguishes the L/C payment method is the involvement of banks as